A new species of Pavonia (Malvaceae) from the Atlantic coastal forests of eastern Brazil - Fryxell, Paul A. (Phytotaxa, 2009)
Pavonia paucidentata is described, adding a new species to Pavonia subgenus Goetheoides, a group that is endemic to the wet coastal forests of easternmostBrazil. This increases the number of species in the subgenus to 27, which is considered to be a high level of diversity for arborescent species in this geographically and ecologically limited area.